2011
DOI: 10.1007/s11357-011-9344-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of honeybees reared in a thermostatic chamber for aging studies

Abstract: Honeybees (Apis mellifera) are an attractive model system for studying aging. However, the aging level of worker honeybees from the field hive is in dispute. To eliminate the influence of task performance and confirm the relationship between chronological age and aging, we reared newly emerged workers in a thermostat at 34°C throughout their lives. A survivorship curve was obtained, indicating that workers can be reared away from the field hive, and the only difference between these workers is age. To confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
(81 reference statements)
2
22
1
Order By: Relevance
“…Similarly, we have found that ATP concentration decreases with age in the trophocytes and oenocytes of worker bees (Hsu and Chan 2013;Chuang and Hsu 2013). In this study, however, the ATP concentration in trophocytes and oenocytes was similar in young and old queen bees.…”
Section: Nad + Nadh and Atp Concentrationscontrasting
confidence: 49%
See 1 more Smart Citation
“…Similarly, we have found that ATP concentration decreases with age in the trophocytes and oenocytes of worker bees (Hsu and Chan 2013;Chuang and Hsu 2013). In this study, however, the ATP concentration in trophocytes and oenocytes was similar in young and old queen bees.…”
Section: Nad + Nadh and Atp Concentrationscontrasting
confidence: 49%
“…Lack of cell division during adulthood, ease of isolation from the abdomen, and convenient manipulation make trophocytes and oenocytes suitable for use in studies of cellular senescence and longevity (Hsieh and Hsu 2011a, b;Hsu and Chan 2013;Chan et al 2011;Chuang and Hsu 2013;Hsieh and Hsu 2013;Hsu and Hsieh 2014;Hsu and Hu 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, ATP concentration in trophocytes and fat cells have also been shown to decrease with advancing age in worker bees reared in a thermostatic chamber at 34°C (Hsu and Chan 2011a), providing further support for the idea that young and old workers reared in a field hive can be used for studying aging. This decrease in ATP concentration in trophocytes and fat cells of older workers is also consistent with previous studies showing that ATP levels decrease with advancing age in the gastric mucosa and muscle of humans (Kawano et al 1991;Conley et al 2000;Petersen et al 2003;Gurd et al 2008), the blood and brains of mice (Jayachandran et al 2005;Joo et al 1999), the erythrocytes of rabbits (Subasinghe and Spence 2008) and cows (Bartosz et al 1982), and the hearts of rats (Guerrieri et al 1996).…”
Section: δψMmentioning
confidence: 63%
“…Furthermore, trophocytes and fat cells are immersed in abdominal body fluid. Thus, antiaging drugs can be screened for their effects on target trophocytes and fat cells by microinjecting them into the body fluid (Hsieh and Hsu 2011a;Hsu and Chan 2011a), adding to the suitability of trophocytes and fat cells as target cells for cellular senescence studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation